Pre-fortis shortening in Czech English: A production and reaction-time study - Skarnitzl, Radek; Šturm, Pavel (Research in Language, 2016)
This study focuses on the production and perception of English words with a fortis vs. lenis obstruent in the syllable coda. The contrast is mostly cued by the duration of the preceding vowel, which is shorter before fortis than before lenis sounds in native speech. In the first experiment we analyzed the production of 10 Czech speakers of English and compared them to two native controls. The results showed that the Czech speakers did not sufficiently exploit duration to cue the identity of the word-final obstruent. In the second experiment we manipulated C and V durations in target words to transplant the native ratios onto the Czech-accented speech, enhancing the fortis–lenis contrast, and vice versa. 108 listeners took part in a word-monitoring task in which reaction times were measured. The hypothesized advantage to items in which the target word (with a fortis or lenis obstruent) was semantically congruent with the following context was not confirmed, and subsequent analyses showed that the words’ frequency of use and the collocations they enter into strongly affect speech processing and correlate to a large degree with the reaction times.